Floating Tone in Èsùkù - Fáladé Ọpéyemí Williams (Britain International for Academic Research (BIAR-Publisher), 2023)
This paper examines floating tone in Èsùkù - one of the dialects of Akpes spoken in Àjọwá community in Àkókó North West local Government area of Òndó State. Scholars have shown that, floating tone performs functions such as: completed action, negation, agreement, genitive marker, etc. In this paper, it is establish that, a floating tone acts as genitive marker in a noun-noun construction and show completed action in a declarative sentence. Findings in this study show that, apart from /ɔní-/ which serves as genitive marker in the speech form, Èsùkù also has a floating high tone [́] as genitive marker in a noun-noun construction. It is observe that, a floating high tone aligns with the final vowel of the first noun (N1) to form a contour which later simplifies to a level high tone. It is observe the elision of V2 in V1#V2 environment in a genitive construction. The theoretical model employed in analyzing the data in this work is the Autosegmental Phonology because of its problem-solving efficiency in the areas of tone, vowel harmony, and nasality. Descriptive research methodology was adopted for this paper. In eliciting data, the researcher visit the community that speaks the speech form under focus. The study contributes to knowledge in the area of tone analysis in Esuku because no work exists in that area.